2020
DOI: 10.1177/1078155220961553
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial nephritis with pembrolizumab: A case report and review

Abstract: Introduction Pembrolizumab is a monoclonal antibody approved for adult patients with advanced non–small-cell lung cancer (NSCLC). Although immune related adverse events are considered to be well tolerated, complications may occur and discontinuation of the treatment could be required. Case report A 62-year old patient diagnosed with advanced non-small cell lung cancer experienced a decline in the renal function after seven cycles with pembrolizumab. Management & outcome: After ruling out other common cause… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Pembrolizumab was a humanized monoclonal anti-programmed death 1 (PD1) pathway antibody that has been extensively investigated in numerous malignancies ( Kwok et al, 2016 ). Pelaez Bejarano et al showed a case of non-small cell lung cancer treated with Pembrolizumab who developed concurrent AKI, which was diagnosed with interstitial nephritis and finally progressed to CKD stage G2-G3, although Pembrolizumab was stopped immediately and hormone treatment was added ( Pelaez Bejarano et al, 2021 ). In situ hybridization and immunohistochemical staining showed that mRNA and protein levels of programmed death ligand-1 (PD-L1) were expressed, though relatively low, in proximal tubules of normal kidney ( Ding et al, 2005 ).…”
Section: Mechanisms Of Paraneoplastic Kidney Injurymentioning
confidence: 99%
“…Pembrolizumab was a humanized monoclonal anti-programmed death 1 (PD1) pathway antibody that has been extensively investigated in numerous malignancies ( Kwok et al, 2016 ). Pelaez Bejarano et al showed a case of non-small cell lung cancer treated with Pembrolizumab who developed concurrent AKI, which was diagnosed with interstitial nephritis and finally progressed to CKD stage G2-G3, although Pembrolizumab was stopped immediately and hormone treatment was added ( Pelaez Bejarano et al, 2021 ). In situ hybridization and immunohistochemical staining showed that mRNA and protein levels of programmed death ligand-1 (PD-L1) were expressed, though relatively low, in proximal tubules of normal kidney ( Ding et al, 2005 ).…”
Section: Mechanisms Of Paraneoplastic Kidney Injurymentioning
confidence: 99%
“…The use of pembrolizumab, a selective humanized IgG4 kappa monoclonal antibody that inhibits the programmed death‐1 receptor, is currently approved by the United States Food and Drug Administration (US‐FDA) and the European Medicines Agency (EMA) as the standard of care across several types of malignancies and different clinical stages. However, different studies demonstrated that in a small percentage of cases (less than 2%), 1 pembrolizumab may cause acute kidney injury (AKI) associated with the development of acute tubular injury, acute interstitial nephritis and minimal change disease. These histopathological conditions leading to AKI development are in line with the kidney toxicity observed in other immune checkpoint inhibitors even though only a few multicentric studies have deep investigated the relationship between immune checkpoint inhibitors dosage and the acute renal grade of dysfunction 2 …”
Section: Introductionmentioning
confidence: 99%